Sistem Ekonomi (Islam) dan Pelarangan Riba dalam Perspektif Historis - Risanda Alirastra Budiantoro; Riesanda Najmi Sasmita; Tika Widiastuti (ITB AAS INDONESIA Surakarta, 2018)
Allah has given the guidance in the form of Islam for Muslim to take and lead all the aspects of life including the economic activity. The Islamic economic system is believed to be the answer of the economic problems that exist at this time. The goal is to achieve falah in kaffah by not doing some economic activities that are in violation as prescribed by Islam. For example is riba. Discourse on riba can be said